DEVELOPING STUDENTS’ SPEAKING WORKSHEET BASED ON SCIENTIFIC APPROAH FOR GRADE X SENIOR HIGH SCHOOL TELADAN MEDAN - Inriwati Saragih; Masitowarni Siregar; Nora Ronita Dewi (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2018)
The objective of this research was to develop the appropriate English speaking worksheet based on scientific approach for grade X of Senior High School students. This research belongs to Research and Development (R&D) study through seven phases; gathering information and data, analyzing the data, writing the course grid, writing the first draft, getting the experts’ judgement, revising the worksheet and writing the final draft. The subject of this research were 42 students of grade X Senior High School Teladan Medan. There were two questionnaires employed[1] in this research: (1) need analysis questionnaire which distributed to the students and (2) worksheet evaluation questionnaire which distributed to the worksheet experts to evaluate the speaking worksheet. The data obtained from the need analysis questionnaire were analyzed using frequency and percentage, while the data from evaluation questionnaire were analyzed using descriptive statistic. This research developed six units of speaking worksheet. The speaking worksheet for grade X students of Senior High School Teladan Medan consists of Observing, Questioning, Exploring, Associating and Communicating stages. Based on the experts’ judgement of the content, the language, the presentation and the graphic, the develop speaking worksheet is appropriate to be used for grade X students’ of Senior High School Teladan Medan. The mean score of all aspects was 4.68 and chategorized as “very good” since the range was in interval 4.5.<X ≤ 5. Keywords : Research and Development (R&D), Speaking Worksheet, Scientific Approach